Lasertherapy in the adjuvant treatment of tissue necrosis resulting from the use of dermal fillers (Research, Society and Development, 2023)
The increase in life expectancy of the population has brought to light the effects of skin aging and has awakened interest in skin rejuvenation treatments. Soft tissue fillers with hyaluronic acid rank second among minimally invasive aesthetic procedures, second only to the application of botulinum toxin. The widespread use of dermal fillers to achieve rejuvenation has led to an increase in reports of associated complications. In cases of vascular damage with hyaluronic acid fillers, early and intensive use of hyaluronidase is highly recommended to limit tissue compromises. Laser therapy appears as the therapy of choice in the treatment of wound injuries because it considerably reduces healing time, has antimicrobial action and increases local blood circulation. The objective of this work is to offer a literature review to base professionals on the study of complications arising from facial fillers and serve as a basis for future studies in the area. It is concluded from this literature review that, although fillings with hyaluronic acid are considered a safe procedure, the professional needs to be qualified and deeply know anatomy and injectable materials. Detecting the first signs of intercurrences and acting earlier has proven to be extremely important, in addition to knowing how to use the best therapeutic measures, which can prevent irreversible damage to the patient.